Just bananas? a fair trade alternative for small-scale producers in the Dominican Republic - Shreck, Aimee, author; Murray, Douglas L., advisor; Raynolds, Laura, committee member; Taylor, Pete, committee member; Stevis, Dimitris, committee member (Colorado State University. Libraries, 2002)
The Fair Trade movement is one of a growing number of contemporary social movements that have emerged to contest the neoliberal, capitalist, and corporate driven process of globalizadon. The movement seeks to draw from a rising consumer consciousness in the North to improve agricultural conditions in the South by altering exploitative trade relations that govern global exchange. This dissertation questions the extent to which Fair Trade may be a powerful force for overcoming inequitable trade relations, or whether it presents yet another empty promise of capitalist penetration of producer/consumer relations.

The study draws on field work in the Azua Valley of the Dominican Republic and focuses on the level of production to better understand the implications of Fair Trade initiatives. Primary data includes interviews with a random sample of the Fair Trade banana producers in the region (n=115), participant and non-participant observations, and in-depth field interviews with a range of actors involved in the Fair Trade banana initiative.

In addition to examining the implications of Fair Trade for producers involved, I also consider the potential these initiatives might hold for achieving the movement’s more ambitious goal of altering the current system of international trade. I argue that the Fair Trade movement is a counter-hegemonic social movement which can be understood as part of a broader, Gnunscian “war of position.” However, while it successfully redistributes material resources to small-scale commodity producers, the movement's transformative potential is limited in important ways, notably by its reproduction of the historical power asymmetry between North and South. My analysis proceeds from an assumption that many Fair Trade advocates seek substantive, qualitative, and transformative change in the political economy of food and agriculture. But, given the present limitations for Fair Trade initiatives to bring about this kind of change, I argue they need to revisit the way Fair Trade is conducted today. In order to take advantage of its possibilities, the Fair Trade movement must engage in a critical reflection to re-conceptualize what underlies the notion of Fair Trade.
Keywords: social structure; agriculture; initiatives; studies; food; trends; coffee; labeling; consumer relations; ethics; bananas; neoliberalism; social activism; case studies; certification; copyright; handicrafts; coffeehouses